Teachers' perception about the difficulty and use of programming and robotics in the classroom - Ortega-Ruipérez, Beatriz; Lázaro Alcalde, Miguel (Interactive learning environments, 2022)
Programming and robotics are resources that can be used as a learning tool for understanding content. However, some teachers are unmotivated due to preconceptions about their difficulties, which hinder their learning and subsequent application in the classroom. This study aims to determine the perception of 195 teachers teaching different grade levels and areas of knowledge on the learning of programming, robotics, and their possibilities of applying them in the classroom. The results show no differences according to the educational stage to perceive adequate skills to learn programming and robotics, although, by area, the teachers of STEAM are considered more capable than the rest. Regarding the introduction of these resources in the classroom, there are no differences according to educational stage. As for differences by area, STEAM teachers stand out, followed by generalist teachers at lower levels (kindergarten and basic school), while there is greater reluctance among teachers of non-STEM areas at higher levels (high school and university and others). It is concluded that the initial perception is similar for teachers of different stages, and with differences with respect to the area, having interesting repercussions on the design of courses.
Keywords: teacher education; programming; educational robotics; teacher attitudes; JCR; Scopus